Changes in Fecal Carriage of Extended-Spectrum β-Lactamase Producing Enterobacterales in Dutch Veal Calves by Clonal Spread of Klebsiella pneumoniae - Bello Gonzalez, Teresita d.J.; Kant, Arie; Dijkstra, Quillan; Marcato, Francesca; van Reenen, Kees; Veldman, Kees T.; Brouwer, Michael S. M. (Frontiers in Microbiology, 2022)
This study aimed to characterize the changes in fecal carriage of Extended-Spectrum β-Lactamase (ESBL) producing Enterobacterales (ESBL-PE) in a single Dutch veal calves. During the rearing period at the Dutch veal farm, a decrease in fecal carriage of cefotaxime-resistant Escherichia coli isolates was observed after two weeks at the veal farm while an increase of cefotaxime-resistant Klebsiella pneumoniae isolates was demonstrated. E. coli and K. pneumoniae were isolated from rectal swabs collected from 110 veal calves in week 2, 6, 10, 18, and 24 after their arrival at the farm. ESBL-PE isolates were selectively cultured and identified by MALDI-TOF. ESBL genes were characterized by RT-PCR, PCRs, and amplicon sequencing. A total of 80 E. coli and 174 K. pneumoniae strains were isolated from 104 out of 110 veal calves. The prevalence of ESBL-E. coli decreased from week 2 (61%) to week 6 (7%) while an unexpected increase in ESBL-K. pneumoniae colonization was detected in week 6 (80%). The predominant ESBL genes detected in E. coli isolates were blaCTX-M-15 and the non-ESBL gene blaTEM-1a, while in K. pneumoniae blaCTX-M-14 gene was detected in all isolates. Four cefotaxime-resistant K. pneumoniae isolates were randomly selected and characterized in deep by transformation, PCR-based replicon typing, and whole-genome sequencing (WGS). The clonal relatedness of a subgroup of 9 animals carrying K. pneumoniae ESBL genes was investigated by Multi Locus sequence typing (MLST). In four ESBL-K. pneumoniae isolates, blaCTX-M-14 was located on IncFIIK and IncFIINK plasmid replicons and the isolates were multi-drug resistant (MDR). MLST demonstrated a clonal spread of ESBL-K. pneumoniae ST107. To the best of our knowledge, this is the first study to report a change in fecal carriage of ESBL-PE over time in the same veal calf’ during the rearing period.